UJI PUPUK ORGANIK DAN NITROGEN PADA SAWI PAKCOY (Brassica rapa L.) DI LAHAN KERING - Aminah, R. Iin Siti; Marlina, Neni; Idrus, Merisca Dwi Ratna Sari (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2021)
Dryland has the potential for the development of vegetable crops such as Pakcoy, but the problem in dry land is the limited availability of water, the population of microorganisms is very low and the availability of nutrients is low, therefore to optimize the dry land by giving organic chicken manure and nitrogen fertilizer. It is expected that organic chicken manure can increase the activity of microorganisms in decomposing organic fertilizer and provide nutrition and can save water. This study aims to obtain the best dose of organic chicken manure and N fertilizer in increasing pakcoy production. This field research was conducted on farmer's land located on Adas Manis Street, Kebun Bunga Subdistrict, Sukarami District, KM 7 Palembang, South Sumatra Province from May to July 2020. The layout in the field used Factorial RAK with 9 treatment combinations repeated 3 times and 6 sample plants. of each treatment. Factor 1: the dose of organic fertilizer is 5, 10, and 15 tons/ha. Factor 2: urea fertilizer doses are 100, 150, and 200 kg/ha. The highest production of  Pakcoy is found in the combination of giving a dose of organic fertilizer of 15 tons/ha of chicken manure with 150 kg/ha of urea, which is 23,04 ton/ha Lahan kering sangat berpotensi untuk pengembangan tanaman sayuran seperti sawi pakcoy, namun masalah di lahan kering adalah ketersediaan air yang terbatas, populasi mikroorganisme sangat rendah dan ketersediaan nutrisi yang rendah, oleh karena itu untuk optimalkan lahan kering tersebut dengan pemberian pupuk organik kotoran ayam dan pupuk nitrogen. Diharapkan pupuk organik kotoran ayam dapat meningkatkan kegiatan mikroorganisme dalam mendekomposisikan pupuk organik  dan menyediakan nurisi serta dapat menyimpan air.  Penelitian ini bertujuan untuk mendapatkan dosis pupuk organik kotoran ayam dan pupuk N yang terbaik dalam meningkatkan produksi sawi pakcoy.  Penelitian lapangan ini dilakukan di lahan petani yang terletak di jalan Adas Manis Kelurahan Kebun Bunga Kecamatan Sukarami KM 7 Palembang Provinsi Sumatera Selatan dari bulan Mei sampai Juli 2020.  Tata letak di lapangan menggunakan RAK Faktorial  dengan 9 kombinasi perlakuan yang diulang 3 kali dan 6 tanaman contoh dari setiap perlakuan. Faktor 1:dosis pupuk organik yaitu 5, 10 dan 15 ton/ha.  Faktor 2:dosis pupuk urea yaitu 100, 150 dan 200 kg/ha.  Produksi sawi pakcoy tertinggi terdapat pada kombinasi pemberian dosis pupuk organik kotoran ayam 15 ton/ha dengan urea 150 kg/ha yaitu 23,04 ton/ha